(untitled) (PSIKOLOGI KONSELING, 2020)
This aim of this study was to find out whether there is a relationship between social support and resilience of general criminal prisoners at Class II A Correctional Institution Ambarawa. Resilience means that the ability of individuals to adapt the difficulties which they faced, so that they can remain calm and rise from the difficulties. The subject of this study is general criminal prisoners who are in the early adult stage (18-40 years) and has served a half sentence. The data is taken by using quantitative methods with purposive sampling technique. Based on this result of the study has found that the correlation coefficient (r) = 0,269; p < 0.05 with the effect of social support for resilience of 7,23% and 92,77% is influenced by other factors. This study concludes that there is a significant positive relationship between social support and resilience to general criminal prisoners at Class II A Correctional Institutions Ambarawa. Key Words : Social Support, Resilience